Pancasila Student Profile as Achievement Merdeka Belajar on Program Guru Penggerak - Nurihayanti, Onny (Prosiding Seminar, 2022)
The condition of education in Indonesia is currently a very serious concern, especially by the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia. The education system that is considered to have poor quality ultimately forms students who are low in competence and have bad character.  The industrial revolution 4.0 requires students to have the ability to interact with modern technology. However, the era of digitalization has changed the culture of social interaction to become less important, thus changing the eastern character of the Indonesian nation. This problem must be changed and returned to the real philosophy, namely by creating the right strategy through education. The Ministry of Education, Culture, Research and Technology of the Republic of Indonesia overhauled the education system by carrying out the principle of Merdeka Belajar which has a comprehensive implementation stage at all levels of education, one of which is through the Program Pendidikan Guru Penggerak with the final achievement of Strengthening the Pancasila Student Profile. This research is a qualitative study by collecting data from various books and journals as well as through field observations. The results show that the implementation of Freedom to Learning in schools is in accordance with the Indonesian educational philosophy as conveyed by Ki Hajar Dewantara, namely holding the principle of freedom of thought and innovation for teachers and students, providing a fun and student-centered learning atmosphere. Guru Penggerak is one of the agents carrying the mission of Merdeka Belajar who becomes a leader in learning and mobilizes other teacher learning communities to innovate and encourage students to develop according to their talents so that the Student Profile is realized according to the noble values of the Indonesian Nation, namely the Pancasila Student Profile which has a strong character, globally competitive and dignified.